Long-Term Outcomes of Multiligament Knee Injuries. Issue 8 (August 2022) - Zhang, Tina; Shasti, Keyan; Dubina, Andrew; Schneider, Matheus B.; Aneizi, Ali; Packer, Jonathan D.; O'Toole, Robert V.; Sciadini, Marcus F.; Henn, R. Frank
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To characterize long-term outcomes of multiligament knee injuries (MLKIs) using patient-reported outcome measures, physical examination, and knee radiographs. Design: Retrospective clinical follow-up. Methods: Twenty knees (18 patients) were evaluated at a mean follow-up of 13.1 years (range 11–15 years). The primary outcome measure was the Internal Knee Documentation Committee score. Patients also completed secondary patient-based outcome assessments including Patient-Reported Outcomes Measurement Information System computer adaptive testing, Short Form-36, and Tegner activity score. Sixteen knees (14 patients) also had physical examination and bilateral knee radiographs assessed with the Kellgren-Lawrence score. Results: The mean Internal Knee Documentation Committee score was 56 points, which was significantly lower than the age-matched normative value of 77 ( P = 0.004) and exceeds the minimum clinically important difference of 12 points. Most secondary outcome scores were worse than normative population values. Posttraumatic arthritis was present in 100% of MLKIs that had radiographs. Comparing operative versus nonoperative management, there were no statistical differences in patient demographics, injury characteristics, physical examination, or imaging, but surgical patients had better Short Form-36 Social Functioning (89 vs. 63, P = 0.02) and Tegner scores (4.5 vs. 2.9, P = 0.05). Conclusion: The long-term outcomes of MLKIs are generally poor, and posttraumatic radiographic evidence of arthritis seems to be universal. Operative management of these injuries may improve long-term outcomes. Clinicians should be aware of these results when counseling patients. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.